GC-MS Analysis and In-vitro Apoptosis Induction and Anticancer Activity of Methanol Extract of Aspergillus terreusagainst Lung Cancer - G. Sanjotha; C.T. Shivasharana; Arun K. Shettar; Sudheer Manawadi; B.N. Devendra (Journal of Pure and Applied Microbiology, 2022)
The present study was focusing on qualitative and quantification of bioactive compounds present in Aspergillus terreus and evaluating its anticancer activity and apoptosis detection against lung cancer. Methods: A. terreus was sequentially extracted using the Soxhlet extraction technique with hexane, ethyl acetate, methanol and distilled water. Detection of bioactive compounds was done using Standard biochemical tests and GC-MS analysis was performed with NIST database to identify the bioactive compounds. The toxicity and anticancer activity of crude extract was investigated using MTT assay on L929 cells and lung cancer A549 cells whereas apoptosis study was conducted through Flowcytometry-based surface marker study on the A549 cancer cell line. Results: secondary metabolites analysis showed the presence of phenols and terpenoids as major constituents in the methanol extract whereas other solvent extracts have shown the absence of major bioactive compounds. Quantification studies showed that methanol extract has shown the phenolic content 179 µg/g of Gallic acid equivalent. The GC-MS analysis showed the presence of 1-Flurodecane, Methyl palmitate, Ethyl palmitate, 9, 12-Octadecanopic acid, 10-Octadecanoic acid, Methyl stearate, Octadecadeoinoate, Ethyl 9-hexadecanoate and 1-Monoarachidin as major bioactive compounds. Further, MTT based toxicity study on the L929 cell line revealed that methanol extract at lower concentrations like 50µg, 100µg and150µg shown more than 50% of cell viability and at higher concentration between 200µg-250 µg it was showing toxic nature with 47.89±0.01% viability. In case of anticancer activity against lung cancer A549 cell line the methanol extract have shown the dose dependent activity i.e the percentage of cell viability was decreased with increase in the concentration of methanol extract at 250µg the cell viability was found to be 35.12±0.005%. Flow cytometry based apoptosis study revealed that methanol extract has shown the inducing apoptosis in treated lung cancer A549 cells with percentage of 10.84. Conclusion: overall the present study shown that A. terreus possess different class of bioactive compounds and it has higher phenolic content. Toxicity study showed that methanol extract exhibited toxic nature at higher concentration on tested cell line and Anticancer and Apoptosis study revealed that methanol extract has shown the prominent with inhibiting the growth of lung cancer A549 cells through inducing apoptosis. Further, A. terreus would be a promising natural microorganism that has to be further researched in order to discover and isolate potent drug to treat cancer. Future studies will be on study of in-vivo animal studies and study of molecular mechanism of drug action on particular with anticancer study.